2022
DOI: 10.3390/s22041364
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of Hybrid Polymeric Nanoparticles of Apigenin: Physicochemical Characterization, Antioxidant Activity and Cytotoxicity Evaluation

Abstract: Breast cancer is the most common cancer in females and ranked second after skin cancer. The use of natural compounds is a good alternative for the treatment of breast cancer with less toxicity than synthetic drugs. The aim of the present study is to develop and characterize hybrid Apigenin (AN) Nanoparticles (NPs) for oral delivery (AN-NPs). The hybrid AN-NPs were prepared by the self-assembly method using lecithin, chitosan and TPGS. Further, the NPs were optimized by Box-Behnken design (3-factor, 3-level). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…22 The presence of ethanol also contributes to increased permeation by lowering the interfacial tension between the ethosomes and intestinal tissue and thus enhancing the drug contact time with tissue. 27,41 According to the above results, the optimized KMP ethosomes formulation was found to be a suitable carrier system for effective oral, topical, and transdermal applications as per the past literature. 37,[42][43][44]…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…22 The presence of ethanol also contributes to increased permeation by lowering the interfacial tension between the ethosomes and intestinal tissue and thus enhancing the drug contact time with tissue. 27,41 According to the above results, the optimized KMP ethosomes formulation was found to be a suitable carrier system for effective oral, topical, and transdermal applications as per the past literature. 37,[42][43][44]…”
Section: Discussionmentioning
confidence: 56%
“…In accordance with the correlation equation's positive sign of their coefficients, it was shown that a lowering of ethanol concentration and a rise in lipid concentration both significantly increased the PDI. 20,27,32 3.1. depicted in Table 2, may be the reason of decreased ZP. In the formulation with 300 mg of lipid, the ZP of various ethosome formulations ranged from À17.69 ± 0.12 to À34.98 ± 0.4 mV.…”
Section: Optimized Kmp Ethosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…More studies have reported that the combination of apigenin and chitosan may enhance the anti-oxidant activity of both compounds. Zafar et.al investigated the chitosan-based nanoparticles loaded with APG, and results showed enhanced anti-oxidant activity [45]. However, more research is needed to understand the mechanisms underlying this effect fully and to determine the optimal ratios and concentrations of the two compounds for maximizing their anti-oxidant potential.…”
Section: Anti-oxidant Studymentioning
confidence: 99%
“…[21,[100][101][102] These particles are easily bound with negatively charged non-specific cells or proteins, resulting in short survival time and poor passive targeting ability in vivo. [158] Some synthetic materials have cytotoxicity [155,158,159] and low gene transfection efficiency. [160,161] When electrons are not loaded, the electric ablation field of IRE cannot be enhanced, and the ablation range cannot be expanded.…”
Section: Spio-npsmentioning
confidence: 99%